Classification of structural and semantic modifications of the paremiological cliche and the mechanisms of their transformation (Journal of Pedagogical Inventions and Practices, 2024)
This article uses the materials of the doctoral dissertation of the candidate of philological sciences Safronov Elbek Olegovich. The theoretical characterization of proverbs as an object of the theory of language and comparative linguistics is given. This research has no analogues in the world, so it is relevant not only for the scientific field, but also for all mankind. The dissertation research is aimed at fulfilling the tasks noted in the Decree of the President of the Republic of Uzbekistan No. UP–4947 "On the strategy of actions for the further development of the Republic of Uzbekistan [Mirziyoyev, 2017]" dated February 7, 2017 and other normative legal documents adopted in this area, in the Decree of the President of the Republic of Uzbekistan No. PP-2909 dated 20 April 2017 "On measures for the further development of the higher education system" and Resolution of the Cabinet of Ministers of the Republic of Uzbekistan No. 304 dated May 22, 2017 "On measures to further improve the postgraduate education system". This research has no analogues in the world; therefore it is relevant not only for the scientific field, but also for all mankind.